Transforming Growth Factor-β Signaling in Immunity and Cancer - Batlle, Eduard; Massagué, Joan (Immunity (Cambridge, Mass.), 2019)
Transforming growth factor (TGF)-β is a crucial enforcer of immune homeostasis and tolerance, inhibiting the expansion and function of many components of the immune system. Perturbations in TGF-β signaling underlie inflammatory diseases and promote tumor emergence. TGF-β is also central to immune suppression within the tumor microenvironment, and recent studies have revealed roles in tumor immune evasion and poor responses to cancer immunotherapy. Here, we present an overview of the complex biology of the TGF-β family and its context-dependent nature. Then, focusing on cancer, we discuss the roles of TGF-β signaling in distinct immune cell types and how this knowledge is being leveraged to unleash the immune system against the tumor. Massagué and Batlle present an overview of the complex biology of the TGF-β family and, focusing on cancer, discuss the roles of TGF-β signaling in distinct immune cell types and how this knowledge is being leveraged in the clinic.